TRADISI TAROKIN PADA JAMA’AH TAREKAT NAKSABANDIYAH DI DESA KEBUNDURIAN KECAMATAN GUNUNG SAHILAN KABUPATEN KAMPAR RIAU - Amanan Amanan (Ensiklopedia Social Review, 2019)
Islam came to the village of Kebundurian, the district of Gunung Sahilan through Kuntu area which is now part of Kampar Kiri. Meanwhile, Naksabandiyah party came to the district of Gunung Sahilan, the village of Kebundurian from XIII Koto Kampar regency, Kampar regency which was brought by Syekh Ja’far from Pulau Godang. The entrance of Naksabandiyah party brought to this area several kinds of Islamic tradition. One of the tradition is Tarokin tradition. Tarokin (Talkin/Talqin in Arabic word) is a guidance to say the sentence of La Ilaha Illallah that is conducted to someone who is almost dying. This guidance is based on the prophet Muhammad SAW teaching that is “Please guide someone who faces death by saying La Ilaha Illallah”. Meanwhile, for Moslem, Talkin is given for a Moslem corpse who has just been buried. This teaching is to remind him/her the best answers when the Angels of Munkar and Nangkir ask questions. Moslems believe when persons carrying the corpse leave the grave, the Angels will come and ask principal questions to the dead body.